Use of microwave oven in the calcination of MgO and effect on the properties of magnesium phosphate cement. (20th February 2019) - Ribeiro, D.V.; Paula, G.R.; Morelli, M.R.
Highlights: Microwave calcination of MgO and effect of this calcination method is evaluated. Doped and undoped MgO powders were prepared. MgO powders were calcined at different temperatures, heating rates and dwell times. MgO powders prepared under different conditions were characterized. The effects of microwave calcination were positive, especially for doped powders. Abstract: There is significant interest in materials synthesized at room temperature, because they represent an alternative to current energy problems. These include magnesium phosphate cements, moldable ceramics that combine low density and good mechanical strength, obtained in short time intervals. The calcination of magnesium oxide (MgO), required due to its high reactivity with phosphates, increases the cost of processing, and the addition of retarders is required to increase the setting time of these cements. In this study, methods for increasing the setting time of these cements, and the evaluation of alternatives to reduce the calcination temperature of MgO were investigated. The microwave calcination of MgO at 1000 °C, in the presence of absorbers of the radiation, resulted in cements with properties superior to those obtained with conventional calcined powders at 1100 °C. In addition, a heating rate five-times higher and a dwell time four times less than used to conventional firing methods were used. This demonstrates the promising use of additivation and firing in a microwave oven to reduce the calcination temperature of MgO and optimize the properties of the resulting magnesium phosphate cements.